Beykoz Kitâbeleri : Mezarlıklar : Akbaba, Alibahadır, Anadolufeneri, Anadoluhisarı, Anadolukavağı, Atâullah Efendi Hazîresi, Beykoz Çayırı, Edhem Efendi Tekkesi Hazîresi, Çakmak Dede, cilt II - Galitekin, Ahmet Nezih. (İstanbul)
562 s.